Internal and external self-affirmation resources: validation and assessment of psychometric properties of the spontaneous self-affirmation measure using structural equation modeling - Rader, Lena; Gauggel, Siegfried; Drueke, Barbara; Weise, Lorenz; Forster, Saskia Doreen; Mainz, Verena (Frontiers in Psychology, 2024)
Introduction People use coping strategies such as self-affirmation to manage threats to their self-esteem. In empirical research, self-affirmation often involves recalling personal values, strengths, or relationships to restore moral integrity. Research shows it improves attitude adjustment, resolves cognitive dissonance, and enhances well-being. Some studies stress the importance of distinguishing between different aspects of self-affirmation, like strengths or social relations. These aspects align with concepts in psychotherapy that differentiate between internal and external resource activation, benefiting health, self-esteem, and resilience. The aim of the current study was twofold: first, to independently test the three-factor structure of the Spontaneous Self-affirmation Measure (SSAM), and second, to integrate self-affirmation strategies into a broader resource activation framework as resilience factors. It also examined associations with self-esteem and effects of age, gender, and education on spontaneous self-affirmation. Methods 1,100 participants (72% female, age 18–65) were recruited online. The original three-factor structure of the SSAM (with the factors Strengths, Values and Social relations) was examined using structural equation modeling. Further, a theory driven two-factor structure applying an internal and external resources framework was examined, integrating the factors of the SSAM into the taxonomy of resource activation (Internal resources: Strengths and Values; External resources: Social relations). Results The results of confirmatory factor analyses showed that both the original three-factor structure and the complementary two-factor structure with an Internal resources and External resources factor fit the data appropriately. All three factors of the original factor model showed a high reliability (Strengths: ωt = 0.91, Values: ωt = 0.91, Social relations: ωt = 0.92). We also found measurement invariance across age, gender, and education. Furthermore, group differences regarding gender, education and ethnicity in the utilization of spontaneous self-affirmation strategies were apparent. Finally, it was demonstrated that the Internal resources factor of the complementary two-factor model is significantly more strongly correlated with self-esteem than the External Resources factor [z = 12.80, p < 0.001, 95%CIdiff (0.24, 0.33)]. Discussion The study confirms the validity of both the three-factor and two-factor structures of the SSAM. Integrating self-affirmation into the resource activation framework may facilitate applying findings from self-affirmation studies to clinical contexts.